Review of the problem field of the IV All-Russian (with international participation) scientifi c conference "A new generation of professionals in education: Personal development based on the integration of values" - Aleksandrova, Ekaterina A.; Shustova, Lyubov Р.; Danilov, Sergey V. (Saratov State University, 2024)
The research relevance is determined by the raise of the problematic fi eld devoted to the value-based integration of the educational subjects. This problematic fi eld serves as the general idea of the IV All-Russian (with International Participation) Scientifi c Conference “A New Generation of Professionals in Education: Personal Development Based on the Integration of Values” (November 23, 2023, Ulyanovsk State Pedagogical University named after I. N. Ulyanov; Ulyanovsk). Objective: the analytical review of the problematic fi eld of the IV All-Russian (with international participation) scientifi c and practical conference, which was organized and conducted by Ulyanovsk State Pedagogical University named after I. N. Ulyanov in close cooperation with Grodno Regional Institute for Educational Development (Republic of Belarus) and Saratov State University named after N. G. Chernyshevsky. The subject-matter of the traditional scientifi c and practical conference this year actualizes the personalitydevelopment aspect of the young teacher’s activity and in this perspective it develops the logic of the international forum “Humanization of the Educational Space: Culture of the Educating Personality”, held by the Faculty of Psychological, Pedagogical and Special Needs Education of Saratov State University named after N. G. Chernyshevsky on April 19-20, 2023. Results: the conference brought together 192 participants and is aimed in its context at creating conditions for further constructive dialogues between representatives of the scientifi c and pedagogical community, young teachers and students majoring in pedagogy, classroom teachers and mentors on the issue of educating the younger generation and integrating universal values in the process. The originality and novelty of the conference is determined by the format of its various components. This year, the conference venues are represented by the laboratory of Russian pedagogical practices “Educational practices: history and the present-day state”, the methodological laboratory “Professional position of a young teacher in the context of the value transformation”, the laboratory of educational spaces modeling “Young teacher in the personal-development activity”, the laboratory of continuous pedagogical education “Continuity in the fi eld of education: from organization of psychological and pedagogical classes to mentoring practice in education”, and the laboratory of Masters of Education “Professional practices in the work of a young teacher”